Вісті з Міжнародної агропромислової виставки AgroExpo-2019 - Муха, Володимир Миколайович; Литовченко, Олексій Іванович; Куянов, Володимир Вікторович; Миропольський, Олександр Михайлович (My University, 2019)
25-28 вересня 2019 року в місті Кропивницький відбулась одна з найбільших Міжнародних агропромислових виставок – AgroExpo-2019. Виставкова площа комплексу має рекордні для України розміри і складає 125 000 м. На виставці експонувалось велике різноманіття техніки, зокрема: техніка для тваринництва та рослинництва,сучасні трактори, зернозбиральні комбайни, причепи, навантажувачі, техніка для обробітку ґрунту та сівби, розкидачі мінеральних добрив, обприскувачі, обладнання для переробки зернових та олійних культур, елементна база. Окремо було представлено демонстраційні покази техніки в роботі. On September 25-28, 2019, one of the largest AgroExpo-2019 International Agricultural Exhibitions took place in Kropyvnytskyi. The exhibition area of the complex has a record size for Ukraine and is125 000 m. The exhibition exhibited a wide variety of equipment, in particular machinery for animal husbandry and crop production, modern tractors, combine harvesters, trailers, loaders, machinery for cultivation of soiland sowing, mineral spreaders, equipment for processinggrain and oilseeds, element base. Demonstrations of the technique in the work were also presented separately.Within the framework of the agro-industrial exhibition"Pokrovsky Fair" was also organized. At the VII International Agro-Industrial Exhibition with field demonstration of AgroExpo-2019 equipment, 585 exhibitors and about 500 participants of the Pokrovsky Fair participated.
Keywords: сільськогосподарська техніка; виставка-демонстрація; Міжнародна агропромислова виставка; AgroExpo-2019; agricultural machinery; exhibition show; International Agricultural Exhibition; AgroExpo-2019